The Work of Special Education Teachers in the Tiered Support System: The Finnish Case - Paloniemi, Annukka; Pulkkinen, Jonna; Kärnä, Eija; Björn, Piia (Taylor & Francis, 2022)
This study investigated primary school special education teachers’ (SETs’) (N = 283) conceptions on their work descriptions and uses of pedagogical documents after a reform in the national support framework. The respondents of this survey reported working mostly in Tiers 1 and 2 when all their tasks (instruction, consultation, and managerial tasks) were considered. The responsibilities of the SETs were, however, more clearly defined in Tier 3. The SETs allocate their work autonomously, but their work description is related to their workload. Clarifications in work descriptions and further elaboration of school’s tiered support functions, emphasizing collaborative practices, are suggested.